plan de desarrollo Medellin_servidores - Alcaldía de Medellín, Medellín es Solidaria y Competitiva (La Sociología en sus Escenarios, 2010)
Abstract. "Medellín es solidaria y competitiva". Plan of development 2008 - 2011 The Plan is focused in a strategy to diminish the poverty and to improve the quality of life of ample sectors of the population that been have excluded from the dynamic ones and the benefits of the development. Strategic lines Line 1. Medellin, shared in common and equitable city Line 2. Development and well-being for the entire city Line 3. Economic development and innovation Line 4. Habitat and environment for people Line 5. City with regional and global projection Line 6. Democratic institutionalism and citizen participation Resumen. Medellín es solidaria y competitiva. Plan de Desarrollo 2008 - 2011 El Plan se focaliza en una estrategia para disminuir la pobreza y mejorar la calidad de vida de amplios sectores de la población que han estado excluidos de las dinámicas y los beneficios del desarrollo. Lineas estratégicas Línea 1. Medellín, ciudad solidaria y equitativa Línea 2. Desarrollo y bienestar para toda la ciudad Línea 3. Desarrollo económico e innovación Línea 4. Hábitat y medio ambiente para la gente Línea 5. Ciudad con proyección regional y global Línea 6. Institucionalidad democrática y participación ciudadana